2021
DOI: 10.1177/15381927211057764
|View full text |Cite
|
Sign up to set email alerts
|

Examining Field Experiences of Teacher Candidates During COVID-19: Systemic Inequities Unveiled for Underserved English Learners in K-12 Grades

Abstract: The impact of coronavirus disease 2019 challenged schools and credential programs to adjust pedagogy, but rapid changes impeded equitable practices to K-12 grade English Learners (ELs). The framework stems from critical multicultural education. Data represented 81 credential candidates across three universities. Study confirmed that ELs lacked access to online learning, active engagement with peers/teachers, and differentiated instruction due to rapid changes and uncertainties to their programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Research has shown that differentiated instruction has a positive impact on student learning, leading to increased student engagement, improved academic achievement, and greater student satisfaction (Lin et al, 2021). However, despite its potential benefits, implementing differentiated instruction in the classroom can be challenging and requires a lot of planning and preparation (Hernandez et al, 2021). Therefore, it is important to understand the concept of differentiated instruction and the research that supports it in order to effectively implement it in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that differentiated instruction has a positive impact on student learning, leading to increased student engagement, improved academic achievement, and greater student satisfaction (Lin et al, 2021). However, despite its potential benefits, implementing differentiated instruction in the classroom can be challenging and requires a lot of planning and preparation (Hernandez et al, 2021). Therefore, it is important to understand the concept of differentiated instruction and the research that supports it in order to effectively implement it in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, online learning at all levels of education, from kindergarten to tertiary level, is inevitable; all students are doing their best to do distance learning, parents are busy preparing smartphones whose prices are pretty high, even if they buy used ones, students are required to learn independently only learning via cellphone there is no teacher where to ask questions from time to time, the teacher does not know the students well, the students do not know each other either (Hernandez et al, 2021). However, in these circumstances, the teacher still must carry out his obligations as a teacher, where the teacher must ensure that students can obtain information/knowledge to be given to students (Wandini & Lubis, 2021).…”
Section: Online Methods Learningmentioning
confidence: 99%
“…(Garcia et al, 2019;Kotob & Abadi, 2019). Recently, some studies started looking at how differentiated instruction has been impacted amidst the COVID-19 pandemic (Hernandez, et al 2021). Overall, there are useful guidelines for preparing preservice teachers to identify and respond to the different learning needs of CLDS (Jackson & Evans, 2017;Partami, 2019;Smale-Jacobse et al, 2019).…”
Section: Differentiation For Culturally and Linguistically Diverse St...mentioning
confidence: 99%